Chitosan-MOF composite membrane as well as preparation method and application thereof

By combining Co-MOF nanoparticles with chitosan and other components, a chitosan-MOF composite film with multiple properties was prepared, which solved the complex, time-consuming and instability of existing natural colorants in the extraction process, and achieved efficient and low-cost intelligent packaging materials.

CN119708565APending Publication Date: 2025-03-28LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411879949.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The extraction process of existing natural colorants is complex and time-consuming, increasing costs, and unstable in the photothermal environment, affecting the accuracy of color changes, making it difficult to meet the needs of smart packaging materials.

Method used

Using the preparation method of chitosan-MOF composite film, by combining Co-MOF nanoparticles with components such as chitosan, a composite film with mechanical properties, hydrophobic properties, barrier properties, ammonia response properties and antibacterial properties is formed.

Benefits of technology

It enhances the mechanical properties and barrier properties of the composite film, improves the response sensitivity to ammonia and antibacterial ability, meets the actual needs of food preservation packaging, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708565A_ABST
    Figure CN119708565A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preservation, and particularly relates to a chitosan-MOF composite film and a preparation method and application thereof. The preparation method comprises the following steps: (I) preparing nanoparticles; and (II) preparing the chitosan-MOF composite membrane. In the preparation process, different proportions of Co-MOF are added into the chitosan-based film, so that the mechanical property, hydrophobic property, barrier property, ammonia response property, antibacterial property and the like of the chitosan-based film are enhanced, the enhanced CS / MOF film can meet the practical application of subsequent fresh-keeping packaging, and a foundation is laid for fresh-keeping research of fresh meat, fruits, vegetables and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fresh-keeping, and specifically relates to a chitosan-MOF composite film and a preparation method and application thereof. Background Art

[0002] In recent years, smart packaging films based on pH or ammonia-sensitive biopolymers have emerged. They can change color with the alkaline substances released by food spoilage, realizing real-time monitoring of freshness. This packaging film is composed of degradable biopolymers and natural colorants. Natural pigments from a variety of plant sources have been used to manufacture such smart packaging materials to improve the level of food safety monitoring. Taking the research of Ezati et al. as an example (Ezati P, Bang Y, Rhim J. Preparation of a shikonin-based pH-sensitive color indicator for monitoring the freshness of fish and pork [J]. Food Chemistry. 2021, 337, 127995), they successfully combined pH / ammonia-sensitive shikonin with cellulose paper to develop smart packaging materials that can monitor the freshness of fish and pork. However, although natural colorants have advantages, they also have some disadvantages. Their extraction process is complicated and time-consuming, which increases costs; their stability is affected in light and heat environments, which affects the accuracy of color changes. Therefore, it is urgent to develop new ammonia-sensitive smart packaging materials with the characteristics of stability and low cost.

[0003] Metal-organic frameworks (MOFs), as an emerging organic-inorganic hybrid material, are constructed by metal nodes and organic linkers through coordination reactions and have broad application prospects. Due to their long-term stability, tunable functions and easy manufacturing, MOFs have been widely used in many fields such as drug delivery, biomedicine, gas adsorption and sensing, and packaging industry. It is worth mentioning that MOFs usually have good compatibility with biopolymer matrices due to their inorganic-organic hybrid properties, which makes them ideal fillers for making composite materials. By adding MOF crystals as functional fillers, the properties of composite materials such as mechanical strength, ultraviolet (UV) shielding ability and flame retardancy can be enhanced. However, despite the many advantages of MOFs, research on exploring ammonia-sensitive MOF crystals as functional fillers is still relatively scarce.

[0004] Chitosan (CS) is a high-quality polysaccharide with excellent biodegradability and film-forming properties, and is antibacterial and low-toxic. It is rich in amino groups and can be grafted with functional molecules to enhance its performance, making it suitable for food packaging. However, pure CS film is lacking in toughness, strength, waterproofness, UV resistance, and antibacterial properties, which limits its application.

[0005] Therefore, based on this, the technical solution of the present invention is proposed. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a chitosan-MOF composite membrane, the preparation method comprising the following steps:

[0007] (I) Preparation of nanoparticles:

[0008] (1) dissolving 1,3,5-benzenetricarboxylic acid in N,N-dimethylformamide solution to obtain a mixed solution A;

[0009] (2) dissolving cobalt acetate tetrahydrate and lauric acid in anhydrous ethanol to obtain a mixed solution B;

[0010] (3) adding the mixed solution A dropwise to the mixed solution B, stirring and centrifuging to obtain a precipitate; and washing and drying the precipitate to obtain Co-MOF nanoparticles;

[0011] (II) Preparation of chitosan-MOF composite membrane:

[0012] (4) adding the Co-MOF nanoparticles into deionized water to prepare a suspension;

[0013] (5) adding chitosan, glacial acetic acid and glycerol to the suspension, stirring evenly to obtain a chitosan-MOF mixed solution;

[0014] (6) mixing beeswax (BW) and Span 40 with deionized water to dissolve, and then homogenizing to obtain a homogenous solution;

[0015] (7) The chitosan-MOF mixed solution and the homogenous solution are uniformly mixed and then dried to form a film, thereby obtaining the chitosan-MOF composite film.

[0016] Preferably, in step (3), the stirring method is: magnetic stirring at room temperature for 10 to 12 minutes.

[0017] Preferably, in step (3), the cleaning method is: washing with anhydrous ethanol.

[0018] Preferably, in step (3), the drying temperature is 55-60°C.

[0019] Preferably, in step (4), the Co-MOF nanoparticles are added to deionized water, firstly magnetically stirred for 30 to 35 minutes, and then ultrasonicated for 5 to 7 minutes to obtain a suspension.

[0020] Preferably, in step (5), the mass ratio of the Co-MOF nanoparticles in the suspension to the chitosan is 2 to 8 wt %.

[0021] Preferably, in step (6), the temperature of the mixed dissolution is 65-70°C;

[0022] And / or, the homogenizing rotation speed is 16000r / min.

[0023] Preferably, in step (7), the drying temperature is 35-40°C.

[0024] Based on the same technical concept, another embodiment of the present invention is to provide a chitosan-MOF composite membrane obtained by the above preparation method.

[0025] Based on the same technical concept, another solution of the present invention is to provide an application of a chitosan-MOF composite film in the preparation of fresh-keeping packaging products.

[0026] The beneficial effects of the present invention are:

[0027] During the preparation process of the present invention, different proportions of Co-MOF are added to the chitosan-based film to enhance the mechanical properties, hydrophobic properties, barrier properties, ammonia response properties and antibacterial properties of the chitosan-based film, so that the enhanced CS / MOF film can meet the practical application of subsequent fresh-keeping packaging, laying the foundation for the preservation research of fresh meat, fruits and vegetables, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 is a SEM image of chitosan-MOF composite membrane; wherein: Figure 1 A is the SEM images of MOF, CS, CS / MOF-2, CS / MOF-4, CS / MOF-6, and CS / MOF-8 composite films; Figure 1 B is the fracture cross-sectional view of CS, CS / MOF-2, CS / MOF-4, CS / MOF-6 and CS / MOF-8 composite membranes.

[0030] Figure 2 is the FTIR spectrum; where: Figure 2 A is the FTIR spectrum of MOF before and after ammonia reaction; Figure 2 B is the FTIR spectra of CS, CS / MOF-4, and CS / MOF-8 composite films.

[0031] Figure 3are representative XRD patterns of CS and CS / MOF films.

[0032] Figure 4 The graphs are TGA (A) and DTG (B).

[0033] Figure 5 This is a graph showing the mechanical properties test results of the CS / MOF composite membrane.

[0034] Figure 6 It is the toughness test chart of the composite film.

[0035] Figure 7 It is the result graph of water vapor permeability coefficient and oxygen permeability coefficient of CS / MOF composite membrane.

[0036] Figure 8 This is a physical picture of the static water contact angle of the CS / MOF composite membrane.

[0037] Fig. 9 It is the UV-visible spectrum of CS / MOF composite film.

[0038] Fig.10 is the antibacterial property of MOF nanoparticles and CS / MOF membranes.

[0039] Fig.11 These are photos of MOF samples before and after exposure to an ammonia atmosphere.

[0040] Fig.12 It is the color change diagram of CS / MOF composite membrane in response to ammonia.

[0041] Fig.13 is the ΔE value of CS / MOF composite membrane in ammonia atmosphere.

[0042] Fig.14 These are photos of the degradation of CS and CS / MOF composite films in soil at different times.

[0043] Fig.15 This is the result of the cobalt ion release test of CS / MOF composite membrane. DETAILED DESCRIPTION

[0044] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0045] The main reagents and test instruments used in the examples are shown in Table 1 and Table 2, respectively.

[0046] Table 1 Test reagents

[0047] Reagents Specification Manufacturer Chitosan Analytical grade Shanghai McLean Biochemical Technology Co., Ltd. White Beeswax Analytical grade Shanghai McLean Biochemical Technology Co., Ltd. Class 40 Analytical grade Shanghai McLean Biochemical Technology Co., Ltd. Lauric acid Analytical grade Shandong West Asia Chemical Industry Co., Ltd. 1,3,5-Benzenetricarboxylic acid Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. glycerin Analytical grade Sinopharm Chemical Reagent Company Acetic acid Analytical grade Xilong Science Co., Ltd. Anhydrous ethanol Analytical grade Xilong Science Co., Ltd. N,N-Dimethylformamide Analytical grade Xilong Science Co., Ltd.

[0048] Table 2 Test instruments

[0049]

[0050]

[0051] Example 1

[0052] This embodiment provides a method for preparing a chitosan-MOF composite film, the preparation method comprising the following steps:

[0053] (I) Preparation of nanoparticles:

[0054] (1) Dissolve 0.25 g of 1,3,5-benzenetricarboxylic acid in 9.6 mL of N,N-dimethylformamide solution to obtain a mixed solution A;

[0055] (2) dissolving 0.15 g of cobalt acetate tetrahydrate and 1 g of lauric acid in 96 mL of anhydrous ethanol to obtain a mixed solution B;

[0056] (3) adding the mixed solution A dropwise to the mixed solution B, stirring magnetically at room temperature for 10 min, and then centrifuging to obtain a precipitate; washing the precipitate with anhydrous ethanol, centrifuging again, repeating three times, and finally drying in an oven at 55° C. to obtain Co-MOF nanoparticles;

[0057] (II) Preparation of chitosan-MOF composite membrane:

[0058] (4) 2 wt% (based on the mass of CS) of the Co-MOF nanoparticles were dispersed in 67 mL of deionized water, magnetically stirred for 30 min, and ultrasonicated for 5 min until a suspension was obtained;

[0059] (5) 1.15 g of chitosan powder was added to the suspension, followed by 0.5 wt % glacial acetic acid, and finally 0.34 g of glycerol, and the mixture was stirred magnetically for 1 h to obtain a chitosan-MOF mixed solution;

[0060] (6) Add 0.43 g of beeswax and 0.25 g of Span 40 to 10 mL of deionized water and heat to dissolve, stir in a 70°C water bath for 1 h, and homogenize with a homogenizer at a speed of 16000 r / min to obtain a homogenous solution;

[0061] (7) The homogenate solution and the chitosan-MOF mixed solution were mixed and stirred for 5 h, and then the solution was poured into a 60×60 mm plastic culture dish and dried at 40 °C for 10 h to obtain a chitosan-MOF composite membrane.

[0062] In this example, the obtained chitosan-MOF composite membrane is named "CS / MOF-2", wherein "2" indicates that the loading amount of Co-MOF in step (4) is 2 wt%. This naming rule also applies to the following.

[0063] Example 2

[0064] This embodiment provides a method for preparing a chitosan-MOF composite membrane, which is different from Embodiment 1 in that, in step (4), 4 wt % (based on the mass of CS) of Co-MOF nanoparticles are dispersed in 67 mL of deionized water.

[0065] The remaining operations were the same as in Example 1, and the chitosan-MOF composite membrane finally obtained was named “CS / MOF-4”.

[0066] Example 3

[0067] This embodiment provides a method for preparing a chitosan-MOF composite membrane, which is different from Embodiment 1 in that, in step (4), 6 wt % (based on the mass of CS) of Co-MOF nanoparticles are dispersed in 67 mL of deionized water.

[0068] The remaining operations were the same as in Example 1, and the chitosan-MOF composite membrane finally obtained was named “CS / MOF-6”.

[0069] Example 4

[0070] This embodiment provides a method for preparing a chitosan-MOF composite membrane, which is different from Embodiment 1 in that, in step (4), 8 wt % (based on the mass of CS) of Co-MOF nanoparticles are dispersed in 67 mL of deionized water.

[0071] The remaining operations were the same as in Example 1, and the chitosan-MOF composite membrane finally obtained was named “CS / MOF-8”.

[0072] Test example: Structural characterization and performance analysis of chitosan-MOF composite membrane

[0073] 1. Scanning electron microscopy (SEM)

[0074] The surface morphology and fracture cross-section of the CS / MOF composite film were observed using a scanning electron microscope at an accelerating voltage of 10 kV.

[0075] (ii) Fourier transform infrared spectroscopy (FTIR)

[0076] Using an infrared spectrometer at 4000 cm -1 Up to 400cm -1 The test was carried out in the wavelength range.

[0077] (III) X-ray diffraction (XRD)

[0078] The XRD spectrum of the composite film was obtained by X-ray diffractometer with a scanning range of 2θ=5-80° and a scanning rate of 1° / min.

[0079] (IV) Thermogravimetric analysis

[0080] The thermal stability of the composite membrane was tested using a thermogravimetric analyzer in the temperature range of 30-600°C with a nitrogen purge rate of 50 mL / min.

[0081] (V) Mechanical properties

[0082] Fix the film strip on the tensile testing machine, record the initial length L0 (m) of the composite film, measure the difference ΔL (m) between the maximum length and the initial length when the film breaks, and the maximum tensile force F (N) when the film breaks, and make three parallel tests for each sample. The tensile strength is calculated according to the following formula:

[0083]

[0084] Where: TS is the tensile strength of the membrane, MPa; F is the maximum tensile force that the membrane withstands when it breaks, N; D is the membrane thickness, mm; B is the membrane width, mm.

[0085] The elongation at break is calculated according to the following formula:

[0086]

[0087] Where: EAB is the elongation at break, %; ΔL is the difference between the length at break and the initial length, mm; L0 is the initial length of the membrane, mm.

[0088] When measuring the puncture strength, the film is cut into semicircles and fixed between the clamps so that it is located below the test probe. A needle probe with a diameter of 2 mm descends at a speed of 60 mm / min and pierces the film. The maximum puncture force is recorded and the average value is taken after 3 times of repeating. The puncture strength is calculated according to the following formula:

[0089]

[0090] Where F is the maximum puncture force and L is the average thickness of the composite film.

[0091] (VI) Hydrophobicity and oxygen barrier properties

[0092] Refer to the methods in the prior art. Dry 3g of crushed anhydrous calcium chloride in an oven at 100°C for 2h, then quickly put it into a dryer to cool for use. Select an undamaged, flat membrane, measure the thickness, and cover the mouth of the beaker containing calcium chloride and seal it. Place the beaker in a dryer filled with distilled water, set to 25°C and 100% relative humidity, and balance for 2h. Take it out and weigh it at regular intervals. The weighing time each time should not exceed 1% of the test interval. After weighing, shake it gently to mix and put it back. Make sure that the moisture absorption increase does not exceed 10% of the weight of calcium chloride. Measure three times for each group and take the average value. The water vapor permeability coefficient is calculated according to the following formula:

[0093]

[0094] Where: Δm is the mass increment of water vapor permeating through the membrane in the beaker within time t, g; d is the membrane thickness, cm; A is the effective area of ​​the composite membrane for water vapor permeation, cm; t is the time interval between two times after the mass increment stabilizes, h; ΔP is the water vapor pressure difference on both sides of the membrane, KPa. At 25°C, the saturated water vapor pressure of pure water is 3.1671KPa.

[0095] The water contact angle of the composite film samples was measured and photographed at room temperature using DigiddropDX. Each sample was repeated 3 times to obtain the average value.

[0096] The oxygen permeability coefficient (OP) was measured using a gas permeability meter. The shortest side was 105 mm. The test gas was 99% pure oxygen and the total permeability area of ​​the sample was 115.44 cm 2 , take the average value of 3 test data.

[0097] (VII) Light-shielding performance

[0098] The UV-visible (UV-vis) barrier properties of CS composite films with different addition amounts were analyzed using a UV-visible spectrophotometer in the wavelength range of 200-800 nm with air as reference. All film samples were cut into 40 mm × 10 mm and fixed in a quartz spectrophotometer cell.

[0099] (VIII) Antibacterial properties

[0100] Gram-negative bacteria Escherichia coli, Salmonella enterica and Gram-positive bacteria Staphylococcus aureus and Listeria monocytogenes were selected as test bacteria, and the antibacterial properties of Co-MOF nanoparticles, CS, CS / MOF-2, CS / MOF-4, CS / MOF-6, and CS / MOF-8 against the test bacteria were evaluated by the Oxford Cup inhibition test. 7 Then, the Oxford cup was placed on the culture medium, 300 μL of the membrane solution was injected into the Oxford cup, and then cultured at 37°C for 24 h, and the diameter of the inhibition zone was measured.

[0101] (IX) Intelligent ammonia response performance

[0102] The response of the CS / MOF membrane to volatile ammonia was tested with reference to the methods in the prior art and appropriate adjustments were made. 20 mL of ammonia water was placed in a beaker at the bottom of a closed container, and a thin film (20×20 mm) was placed 1 cm above the liquid surface. The color change of the composite membrane over a period of time was observed by taking a photo, and its color change was recorded with a colorimeter, and the ΔE value was recorded.

[0103] (10) Biodegradability

[0104] Referring to the methods in the prior art, the degradation of the composite film was characterized under natural conditions. 12×12 mm samples were marked and buried in natural soil. The samples were taken out within a certain time range, the surface soil was wiped clean, and photos were taken to observe the degradation.

[0105] (XI) Safety

[0106] To test the cobalt ions released from the CS / MOF membrane samples, each membrane sample (diameter: 24 mm) was added to 20 mL of deionized water (food simulant), placed in a shaker, and shaken at 100 rpm and 25 ° C for 48 h. Then, the amount of cobalt ions released into the water was measured by spectrophotometer using nitroso-R-salt. First, 10 mL of the above leaching solution was extracted, and then 15 mL (1.75 mol / L) of phosphoric acid and 15 mL (1.84 mol / L) of sulfuric acid were mixed, and the volume was adjusted to 100 mL volumetric flask with deionized water. The mixed acid solution in 0.8 mL volumetric flask was taken out and mixed with the leaching solution, and then 4 mL of 0.2 wt% nitroso-R salt aqueous solution and 4 mL of sodium acetate aqueous solution (6.09 mol / L) were added, and the water bath was heated to boiling, and then 2 mL of nitric acid (15.8 mol / L) was added, and boiling was continued for 1.5 min. After cooling, the transmittance of the solution at 540 nm was recorded on a UV-Vis spectrophotometer. The release of cobalt was measured from a standard curve prepared in the assay and the results were expressed as the concentration of cobalt ions released into the medium.

[0107] 12. Data Analysis

[0108] All experiments were repeated three times to obtain the final data, and the results were averaged and expressed as mean ± standard deviation. The original data were processed using Excel, SPSS software was used for variance analysis, t-test was used for variance analysis (ANOVA), and Origin software was used to draw graphs.

[0109] Results and Discussion

[0110] (I) SEM results

[0111] The microstructure of the film surface can be observed more accurately by scanning electron microscopy. Figure 1 It can be seen that the synthesized Co-MOF has a nanosheet morphology and is in the form of hexagonal sheets. The CS film has a smooth and dense surface, and the uniformity of the structure is obvious (such as Figure 1 After the addition of MOF, the compactness of the membrane was maintained, but a slight change in surface smoothness was observed, and a few particles appeared on the membrane surface, indicating that MOF successfully combined with the CS membrane to form a dense membrane structure. On the other hand, the addition of MOF led to the formation of pores and bubbles in the structure of the CS / MOF membrane. These observations are consistent with the micrographs obtained from the cross-section of the membrane (see Figure 2A). Figure 1B). In addition, it was noted that no obvious agglomeration of MOF nanoparticles was observed in the CS / MOF-4 and CS / MOF-6 composites, indicating that when the amount of MOF was moderate, the MOF nanofillers could be evenly dispersed and there was good compatibility between the CS matrix and the MOF nanofillers. In addition, at a higher loading (8wt%), a small amount of MOF nanoparticle agglomeration and bubbles were observed throughout the CS matrix, which means that the compatibility between the CS matrix and a large amount of MOF nanofillers was poor, and phase separation occurred. The surface microstructure of the film is also different from the cross-sectional microstructure, which may be due to the different arrangement of MOF in the film structure.

[0112] (II) FTIR results

[0113] In order to better analyze the colorimetric response behavior of Co-MOF, Fourier transform infrared spectroscopy (FTIR) was used to study the structural changes of Co-MOF after exposure to volatile ammonia. Figure 2 As shown in A, the synthesized Co-MOF exhibits a characteristic absorption band located at about 3441 cm -1 The absorption band near 1641 cm is attributed to the OH stretching vibration of the absorbed water molecules in Co-MOF. -1 and 1535cm -1 Corresponding to the asymmetric and symmetric stretching vibrations of COO, 1109 cm -1 Corresponding to the Co-OC stretching vibration, 566 cm -1 Corresponding to the Co-O stretching vibration. After Co-MOF was exposed to volatile ammonia, the peak positions of OH and Co-O were red-shifted, which may be due to the formation of new hydrogen bonding interactions between the Co-O group and the volatile ammonia. Based on the above results, it can be inferred that ammonia molecules can be adsorbed by Co-MOF through the formation of hydrogen bonding interactions. This adsorption behavior changes the coordination environment of cobalt ions, thereby causing the characteristic color change of Co-MOF.

[0114] Figure 2 B compares the FTIR spectra of CS and CS / MOF. -1 At 1407cm, the -OH and -NH2 on chitosan overlap to form a broad stretching vibration (CS characteristic peak). -1 The absorption peak at is caused by the in-plane bending vibration of the NH of the primary amine. The characteristic absorption band of chitosan film is close to 1568 cm -1 , corresponding to the NH-bending (amide II) vibration. The CS film has a peak at 2848 and 2922 cm -1 There are two obvious peaks between them, which are the asymmetric and symmetric stretching vibrations of the aliphatic CN- groups in the fatty acid chains of beeswax, indicating that beeswax was added to the film. -1The intensity of the broad peak nearby is stronger in the CS film than in the CS / MOF film, and the absorption wavelength decreases. This change can be attributed to the plasticizing effect of glycerol, but the plasticizing effect of glycerol is weakened in the CS / MOF composite film. It can be concluded that beeswax is well mixed with the chitosan matrix, and the barrier effect of long-chain fatty alcohols and alkanes in beeswax effectively reduces the content of free hydroxyl groups in the matrix.

[0115] When Co-MOF is added, -COO asymmetric stretching (from 1568 to 1560 cm -1 ) and symmetrical stretch (from 1407 to 1417cm -1 ) showed an obvious shift in the absorption peak position, indicating that a coordination interaction was formed between the Co in Co-MOF and the carboxyl group of CS. At the same time, with the increase of MOF content, the OH stretching peak of CS film gradually moved to a lower wave number (from 3311 to 3305 cm -1 ), which indicates the formation of hydrogen bonds between the carboxyl groups in MOF and the oxygen-containing groups (e.g., hydroxyl and carboxyl groups) in the CS matrix.

[0116] (III) XRD results

[0117] Figure 3 The representative XRD patterns of the synthesized CS and CS / MOF films. In addition, a sharp strong peak can be observed near 2θ=14.7°, indicating that the synthesized Co-MOF has high crystallinity. After adding MOF to the CS film, the intensity of this characteristic peak increased significantly. This result shows that the crystallinity of CS in the CS / MOF film increases, which may be due to the strong hydrogen bonding and electrostatic interactions between CS and Co-MOF, and Co-MOF promotes the close stacking of CS and BW chains. The sharp strong peaks in CS / MOF-NH3 after the ammonia reaction are more obvious, and it is inferred that the ammonia molecules are adsorbed by the MOF in the composite film by forming strong hydrogen bonding interactions.

[0118] (IV) Thermogravimetric analysis

[0119] Figure 4 A. Figure 4 B shows the thermogravimetric analysis (TGA) and differential thermogravimetric (DTG) curves of CS and CS / MOF composite films with different MOF addition amounts, respectively. Figure 4 It can be clearly seen in A that all samples experienced three major weight loss stages. In the first mass loss stage (50-150°C), all films experienced evaporation of water molecules and residual acetic acid during heating, and then the second mass loss stage (150-250°C) occurred mainly due to the volatilization of glycerol. The third mass loss stage (250-600°C) is related to the decomposition of the polymer in the film-forming system.

[0120] The thermal decomposition stability of the composite film can be mainly analyzed by the temperature at which the maximum weight loss rate occurs. Figure 4 B) It can be seen that the degradation range of CS / MOF-8 composite membrane is the most comprehensive because it has the richest composition. The maximum weight loss temperature of CS composite membrane is 296℃, and after adding MOF, the maximum weight loss temperature is reduced, CS / MOF-2 and CS / MOF-8 are reduced to 291℃ and 295℃ respectively, and CS / MOF-4 and CS / MOF-6 are reduced to 278℃. It can be seen that the addition of MOF reduces the thermal stability of CS / MOF composite membrane. This may be due to the destruction of the crystal structure of MOF under high temperature conditions. These changes may lead to the decline of the performance of MOF materials and affect their interaction with polymer matrices such as chitosan. In addition, through thermal analysis of the samples, it was found that after adding MOF, the residual amount of the sample increased significantly, and increased with the increase of the addition amount. At the same addition amount, the residual amount of CS / MOF is significantly greater than that of CS, which may be due to the addition of MOF to increase the density of the composite membrane.

[0121] (V) Mechanical properties

[0122] Mechanical properties are an important indicator of food packaging films. Tensile strength, elongation at break and puncture strength are used to evaluate the effect of MOF nanofillers on the mechanical strength of composite films. Figure 5 As shown, the tensile strength of the CS film is 16.5MPa and the elongation at break is 46%. When 2wt% of MOF is added, the tensile strength of CS / MOF decreases to 13.81MPa. This may be due to the interaction between MOF and CS molecules affecting the two-dimensional structure of the CS composite film, causing the composite film to become brittle. When 6wt% of MOF is added, the tensile strength, elongation at break and puncture strength of CS / MOF all reach the maximum, which are 15.3MPa, 46.64% and 26.91N, respectively. The increase in tensile strength should be attributed to the strong hydrogen bonding interaction between the well-dispersed Co-MOF and the CS matrix, and the cohesive structure of the film is also enhanced, which helps to inhibit phase separation and allow effective stress transfer at the interface. However, when the MOF loading reaches 8wt%, the tensile strength of the film decreases, which may be because a large amount of MOF is more inclined to the formation of intramolecular hydrogen bonds, resulting in the weakening of the intermolecular hydrogen bonding force between the three-dimensional network, the weakening of the cohesive force of the formed composite film, and ultimately the deterioration of the mechanical properties. As Figure 6 As shown, the load-bearing capacity test of the composite film can reach 3kg, which indicates that the composite film has sufficient toughness and tensile strength.

[0123] (VI) Hydrophobicity and oxygen barrier properties

[0124] Water vapor permeability coefficient (WVP) and oxygen permeability coefficient (OP) are important indicators for evaluating the barrier properties of food packaging composite films and have a significant impact on product storage quality. Figure 7 As shown in Figure 2, the CS / MOF-4 and CS / MOF-6 composite films have more effective barrier properties against oxygen and water than the CS film. When the MOF addition amount is 6 wt%, the water vapor permeability coefficient is 0.934×10 -3 g cm / cm 2 ·KPa·h, oxygen permeability coefficient is 6.275cm 3 / m 2 ·24h·0.1MPa. When the MOF content in the composite membrane reaches a certain level, the interaction between molecules is stronger and the cohesive structure of the membrane is also enhanced. The appropriate amount of MOF nanofiller added can reduce the gas permeation through the composite membrane and reduce the oxygen permeability of the membrane material. When the MOF content is 8wt%, the WVP and OP values ​​increase. Combined with the results of scanning electron microscopy, it can be inferred that this is because the MOF content is too high, which causes the cross-linking gap between chitosan and beeswax to be elongated, and the composite membrane agglomerates, destroying the balance of the three-dimensional network structure. The above results show that the addition of 4-6wt% MOF has a certain improvement effect on the barrier properties of CS / MOF membranes.

[0125] The contact angle is a key indicator for measuring the hydrophobicity of composite films. It is affected by the hydrophilicity and hydrophobicity of the substance itself and the properties of the solid surface. These two factors together determine the hydrophobicity of the composite film. One of the important characteristics of food packaging films is the hydrophobicity of the film surface. A contact angle with water greater than 65° can be classified as hydrophobic. Water contact angle (WCA) is Figure 8 As shown in the figure, the results show that CS / MOF-4 and CS / MOF-6 are hydrophobic membranes, and the content of MOF affects the hydrophilicity of the composite membranes. CS / MOF-2 and CS / MOF-8 composite membranes fail to meet the hydrophobic standard.

[0126] Since water molecules will form strong hydrogen bonds with the hydroxyl groups in the CS molecules, the membrane surface is easy to wet, but the CS membrane after adding beeswax, a hydrophobic material, is a hydrophobic membrane. After adding 2wt% of MOF, the hydrophilicity of the composite membrane surface becomes better, so the water contact angle of the membrane material decreases. This is because the presence of a small amount of MOF promotes the formation of hydrogen bonds between components such as chitosan and beeswax, thereby reducing the water contact angle. When the MOF addition amount is in the range of 2-8wt%, as the MOF addition amount increases, the cross-linked network structure is enhanced, and the water contact angle reaches a maximum of 85° when the MOF addition amount is 6wt%. When the MOF content is 8wt%, the contact angle decreases. This may be due to the high MOF content, which leads to the elongation of the cross-linking gap between CS and BW, the agglomeration of the composite membrane, and the destruction of the balance of the three-dimensional network structure. This may also be related to the increase in surface irregularities of the membrane. These irregularities are caused by the presence of natural filler particles. Combined with the results of scanning electron microscopy in the previous article, the surfaces of CS / MOF-2 and CS / MOF-8 are not smooth enough, the surface distribution is uneven, and agglomeration occurs. At the same time, small bubbles appear on the surface. The asymmetric microstructure, bubbles and agglomerated particles in the composite membrane structure weaken the interaction between polymer molecules, resulting in poor hydrophobic properties of these two membranes.

[0127] (VII) Light-shielding performance

[0128] Ultraviolet rays are a common oxidative induction factor in food systems and can easily damage food. Therefore, if packaging materials can effectively prevent the radiation of ultraviolet rays and visible light, it will be one of their most ideal characteristics. Fig. 9 As shown in the figure, the UV transmittance of CS and CS / MOF films at 200nm is extremely low, almost not exceeding 1%, which shows the good UV blocking performance of the composite film at 200nm. The pure CS film shows high transparency in the visible light region, with a maximum transmittance of 43.4% at 600nm and a maximum transmittance of 36.8% at 400nm. After adding MOF, the transmittance of the composite film is further reduced, and the CS / MOF-8 composite film has the best light-shielding performance, with a transmittance of 20.6% at 600nm and 16.8% at 400nm. This may be because the matrix in the composite film forms a dense network structure through molecular interaction, which reduces the transmittance of the composite film and effectively improves the UV resistance of the composite film. When the amount of MOF added increases, the transmittance of the CS / MOF composite film gradually decreases, and the CS / MOF-8 composite film exhibits excellent UV shielding ability. These phenomena indicate that the composite film can shield visible light and ultraviolet light to a certain extent, and the light-shielding performance is optimal when the MOF addition amount is 8wt%.

[0129] (VIII) Antibacterial properties

[0130] The antibacterial property of food packaging film is also an important indicator for evaluating film performance. It can slow down or prevent food spoilage caused by harmful pathogens. The antibacterial activity of MOF against four foodborne pathogenic microorganisms, Staphylococcus aureus, Escherichia coli, Listeria monocytogenes and Salmonella, was determined using the Oxford cup inhibition zone test (Table 3, Fig.10 The size of the inhibition zone indicates that MOF has an effective bactericidal effect on Gram-negative and Gram-positive bacteria. The test results show that MOF has a strong inhibitory effect on Staphylococcus aureus and Escherichia coli, but a weaker inhibitory effect on Listeria monocytogenes and Salmonella, which are 27.65mm, 24.42mm and 21.29mm, 19.36mm respectively (as shown in Table 3). The antibacterial activity of cobalt-based MOFs is generally related to the release of cobalt ions from their surface, because the released cobalt ions have the ability to induce cell membrane damage and bacterial death. Similar antibacterial effects have been observed in other cobalt-based MOFs.

[0131] Table 3 Inhibition zone diameter

[0132]

[0133] Note: Different English letters in superscripts indicate that there are significant differences in the sizes of inhibition zones of the same bacterial species under different treatments (p<0.05).

[0134] The test results also showed that MOF has a better antibacterial effect on Gram-positive bacteria than Gram-negative bacteria, which can be attributed to the difference in their cell wall structures. Gram-positive bacteria have a single peptidoglycan layer and exposed peptide sequences in their cell walls, which promotes strong interactions with MOF, while the thick double-layer peptidoglycan cell wall of Gram-negative bacteria hinders the interaction with MOF. Among them, the CS membrane showed weak antibacterial properties due to chitosan, and the antibacterial effect of the CS membrane mainly originated from the interaction between the positive charge carried by the chitosan molecules and the negative charge of the microbial cell membrane. This interaction causes the leakage of proteins and other key cell components inside the bacteria, which in turn interferes with the normal reproduction process of the bacteria, thereby achieving an antibacterial effect. When the amount of MOF added increased, the CS / MOF composite membrane showed a larger inhibition zone, and the CS / MOF-8 had the largest inhibition zone, with the best effect on Staphylococcus aureus and Salmonella, reaching 16.29mm and 17.6mm, respectively.

[0135] (IX) Intelligent ammonia response performance

[0136] The colorimetric response performance of the prepared Co-MOF nanocrystals was evaluated by exposing them to an ammonia environment for 30 min. Fig.11As shown, the Co-MOF nanoparticles are purple-pink at first and then turn purple-brown after exposure to volatile ammonia. These observations indicate that the prepared MOF nanocrystals have good ammonia-sensitive color-changing properties. Similar colorimetric response behaviors to ammonia have been observed in other cobalt-based MOFs, which are closely related to their adsorption of ammonia and the resulting changes in the coordination environment.

[0137] like Fig.12 and Fig.13 The color response behaviors of pure MOF, CS and CS / MOF composite films to volatile ammonia were measured as shown. Fig.12 It can be observed that both CS and CS / MOF films are uniform and dense to the naked eye, indicating that MOF has good dispersion in the CS matrix. Since Co-MOF is purple-pink, adding MOF to the CS matrix results in a light pink composite film, and the color of the film gradually deepens with the increase of MOF. By exposing the film to an ammonia atmosphere for 30 minutes, the pure CS film shows almost no color change, while the color of the CS / MOF composite film gradually changes from light pink at the beginning to brown-yellow at 30 minutes, and then to brown-black at 120 minutes. The results show that the CS / MOF composite film has a significant color response to ammonia. Combined with the infrared spectrum analysis of the composite film, this may be due to the formation of new hydrogen bond interactions between the Co-O groups in the MOF nanoparticles and the volatile ammonia. Ammonia molecules can be adsorbed by Co-MOF by forming hydrogen bond interactions. This adsorption behavior changes the coordination environment of cobalt ions, resulting in the characteristic color change of Co-MOF, and the composite film with added MOF nanoparticles also changes with the change of MOF color. In the ammonia reaction test, it was also observed that the ΔE values ​​of all CS / MOF-8 composite films increased rapidly from 8.54 to 10.24 within 30 min, which means a rapid and obvious color change behavior that can be recognized by the naked eye. As time increases, the ΔE values ​​of the CS / MOF composite films further increase. After 60 min, the ΔE values ​​of CS / MOF-2, CS / MOF-4, CS / MOF-6, and CS / MOF-8 composite films increased to 5.93, 7.446, 10.37, and 11.59, respectively. These results indicate that the CS blend membranes with high Co-MOF loading have a faster response speed and higher sensitivity to volatile ammonia.

[0138] (10) Biodegradability

[0139] The biodegradability of CS / MOF composite membranes in the natural environment was tested by soil burial degradation method. Fig.14It can be seen that all composite membranes showed a high degradation rate after 42 days of burial, and the degradation rate of CS / MOF composite membrane was lower than that of CS membrane. The reason why CS membrane had the highest degradation rate may be that chitosan is a hydrophilic and degradable material. The moisture in the soil has long penetrated into the polymer network of chitosan and beeswax, weakening the strength of the polymer chain and promoting the hydrolysis of the membrane material. At the same time, the increase in moisture in the composite membrane promotes the growth of microorganisms during the degradation process, which will lead to further degradation of the composite membrane.

[0140] At the same time, it was also found that the late degradation rate of the CS / MOF-2 composite membrane was faster than that of the CS / MOF-4 and CS / MOF-6 composite membranes. The experimental results can be analyzed in conjunction with the results of SEM and WVP in this chapter, because the CS / MOF-4 and CS / MOF-6 composite membranes have smoother membrane surfaces and denser structures than the CS / MOF-2 composite membrane, which can limit the movement of microorganisms and water molecules through the network of the material, thereby increasing the length of the water and microbial paths in the polymer matrix. However, the addition of a large amount of MOF leads to its uneven dispersion in the membrane matrix, forming weak areas, accelerating water absorption and swelling and promoting microbial decomposition. Therefore, due to the dual acceleration of hydrolysis and microbial degradation, the degradation rate of the CS / BW / MOF-8 composite membrane is the highest when the MOF addition is 2-8wt%; and all composite membranes are completely degraded in the soil after 78 days.

[0141] (XI) Safety

[0142] Release test of cobalt ions from CS and CS / MOF composite membranes into deionized water (food simulant). Fig.15 As shown in the figure, the amount of cobalt ion release is greatly affected by MOF. For CS membranes with 2, 4, 6 and 8 wt% MOF, the amount of cobalt ions released into water was 1.62, 4.94, 7.94 and 9.73 μg / mL, respectively. Among these membranes, the CS / MOF-8 composite membrane showed the highest level of cobalt ion release, so it had the strongest antibacterial efficiency against Escherichia coli, Staphylococcus aureus, Listeria monocytogenes and Streptococcus enterica. It is worth noting that even for the CS / MOF-8 composite membrane sample, the total cobalt release mass was only about 9.7 μg, which is far below the acceptable safety amount recommended by the European Food Safety Authority (600 μg / d).

[0143] 12. Conclusion

[0144] The present invention prepares CS / MOF composite membranes with different MOF addition amounts, and conducts detailed research on their microstructure and macroscopic properties.

[0145] (1) The morphology, microstructure and thermal stability of the chitosan / MOF composite membrane were characterized and analyzed. The surface of the CS membrane was smooth and dense from the electron microscope scanning image. After adding MOF, the membrane surface was slightly granular, but the whole was still smooth, indicating that MOF was successfully combined and evenly distributed in the membrane. When the MOF addition amount was 4-6wt%, no obvious agglomeration was observed, showing good compatibility; through infrared spectroscopy and XRD characterization, it was found that MOF was tightly bound to the chitosan matrix through hydrogen bonds, the position of the stretching absorption peak of -COO changed significantly, and the Co in Co-MOF coordinated with the carboxyl group of CS. At the same time, with the increase of MOF, the OH stretching peak of the CS membrane moved to a lower wave number, indicating that hydrogen bonds were formed between the carboxyl group of MOF and the oxygen-containing group of CS; through thermogravimetric analysis, it was found that the maximum weight loss temperature of the CS composite membrane was 296℃. After adding MOF, the maximum weight loss temperature of the composite membrane was reduced, which weakened the thermal stability of the composite membrane.

[0146] (2) The macroscopic properties of the composite membrane were further observed. By analyzing the mechanical properties, hydrophobic properties, barrier properties, antibacterial properties, and intelligent ammonia response properties of the composite membrane, it was found that when the MOF addition amount was 6wt%, the tensile strength, elongation at break, and puncture strength of the composite membrane all reached the maximum values, which were 15.3MPa, 46.64%, and 26.91N, respectively; the water vapor coefficient was 0.934×10 -3 g cm / cm 2 ·KPa·h, oxygen permeability coefficient is 6.275cm 3 / m 2 ·24h·0.1MPa, contact angle is 85°, these indicators are all in the optimal state. It shows that adding 6wt% MOF has a significant improvement effect on the mechanical properties, hydrophobic properties and barrier properties of the composite film. When the MOF addition is 8wt%, the composite film has the best UV shielding effect, and the transmittance is only 16.74% at 400nm, which has excellent light-shielding performance; at the same time, the composite film has good antibacterial properties against Escherichia coli, Staphylococcus aureus, Listeria and Salmonella, and the antibacterial circles reach 12.86mm, 16.29mm, 13.87mm and 17.6mm respectively. The results of the ammonia response test show that the color of the composite film changes significantly, and the ΔE value of the CS / MOF-8 composite film increases rapidly from 8.54 to 10.24 within 30min. It shows that the antibacterial ability and intelligent ammonia response performance of the chitosan / MOF composite film are both optimal under this condition.

[0147] (3) The chitosan / MOF composite film was completely degraded after being buried in the soil for 78 days, indicating good biodegradability. For the CS / MOF-8 composite film with a high MOF addition, the total cobalt release mass was only about 97 μg, which is far lower than the acceptable safety amount recommended by the European Food Safety Authority (600 μg / d), indicating good safety and can be used for food packaging.

[0148] In summary, CS / MOF-6 and CS / MOF-8 composite films exhibit excellent mechanical properties, light-shielding properties, antibacterial properties, and intelligent ammonia response properties, which make them promising food preservation packaging materials in the food industry.

[0149] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a chitosan-MOF composite membrane, characterized in that: The preparation method comprises the following steps: (I) Preparation of nanoparticles: (1) dissolving 1,3,5-benzenetricarboxylic acid in N,N-dimethylformamide solution to obtain a mixed solution A; (2) dissolving cobalt acetate tetrahydrate and lauric acid in anhydrous ethanol to obtain a mixed solution B; (3) adding the mixed solution A dropwise to the mixed solution B, stirring and centrifuging to obtain a precipitate; and washing and drying the precipitate to obtain Co-MOF nanoparticles; (II) Preparation of chitosan-MOF composite membrane: (4) adding the Co-MOF nanoparticles into deionized water to prepare a suspension; (5) adding chitosan, glacial acetic acid and glycerol to the suspension, stirring evenly to obtain a chitosan-MOF mixed solution; (6) mixing beeswax and Span 40 with deionized water to dissolve, and then homogenizing to obtain a homogenous solution; (7) The chitosan-MOF mixed solution and the homogenous solution are uniformly mixed and then dried to form a film, thereby obtaining the chitosan-MOF composite film.

2. The method for preparing the chitosan-MOF composite membrane according to claim 1, characterized in that: In step (3), the stirring method is: magnetic stirring at room temperature for 10 to 12 minutes.

3. The method for preparing the chitosan-MOF composite membrane according to claim 1, characterized in that: In step (3), the cleaning method is: washing with anhydrous ethanol.

4. The method for preparing the chitosan-MOF composite membrane according to claim 1, characterized in that: In step (3), the drying temperature is 55-60°C.

5. The method for preparing the chitosan-MOF composite membrane according to claim 1, characterized in that: In step (4), the Co-MOF nanoparticles are added to deionized water, firstly magnetically stirred for 30 to 35 minutes, and then ultrasonicated for 5 to 7 minutes to obtain a suspension.

6. The method for preparing the chitosan-MOF composite membrane according to claim 1, characterized in that: In step (5), the mass ratio of the Co-MOF nanoparticles in the suspension to the chitosan is 2 to 8 wt %.

7. The method for preparing the chitosan-MOF composite membrane according to claim 1, characterized in that: In step (6), the temperature of the mixed dissolution is 65-70°C; And / or, the homogenizing rotation speed is 16000r / min.

8. The method for preparing the chitosan-MOF composite membrane according to claim 1, characterized in that: In step (7), the drying temperature is 35-40°C.

9. The chitosan-MOF composite membrane obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the chitosan-MOF composite film according to claim 9 in preparing fresh-keeping packaging products.

Citation Information

Cited By

  • La-MOF-COOH / PEI-PVDF composite membrane material for removing phosphorus as well as preparation method and application of La-MOF-COOH / PEI-PVDF composite membrane material

    CN121130670A

  • La-mof-cooh / pei-pvdf composite membrane material for removing phosphorus, preparation method and application

    CN121130670B